Peran Faktor Harga Diri dan Pusat Pengendalian Diri Terhadap Perilaku Seksual Lelaki Seks dengan Lelaki di Jakarta Timur - Nugroho, Adi (Central Basic Biomedical and Health Technology, 2012)
Sexual Behavior among Men who have sex with Men (MSM) gives a large contribution in the chain of transmission of HIV. This study aims to analyze the role of personal factors in MSM in East Jakarta on sexual behavior in particular aspects of self-esteem and locus of control. Research design used quantitative methods with cross sectional approach. Collecting data using purposive sampling technique of 224 respondents in East Jakarta with criteria: had sex with men in the last six months; not a transvestite; able to read and write, and are willing to become respondents. Sexual behavior, self-esteem and locus of controls were measured using self-completion questionnaire by the respondent accompanied by a research assistant. Data analysis was conducted to determine the different proportions of risky sexual behavior based on self-esteem and locus of control. Most respondents have a high-risk sexual behavior (78.1%). About 45.1% of respondents had low self-esteem and 60.7% respondents had locus of control from within themselves. MSM with the locus of control from within has a relatively similar high risk sexual behavior as MSM who had locus of control from outside themselves (p=1.000). MSM with low self-esteem tend to have larger risk for high-risk sexual behavior than MSM who have high self-esteem (OR 1.95% CI 1.00-3.80).Low self-esteem on the MSM tends to increase the risk of their sexual behavior, so that it is recommended to develop methods of counseling and mentoring that contains material to increase self-esteem.Keywords: MSM, sexual behavior, self-esteem, locus of controlÂ AbstrakPerilaku seksual antar pria yang mempunyai hubungan seks Lelaki Seks Lelaki (LSL) memberikan kontribusi besar terhadap rantai penularan HIV. Penyakit ini bertujuan untuk menganalisis faktor personal pada LSL di Jakarta Timur terhadap harga diri dan pusat pengendalian diri. Desain penelitian adalah penelitian kualitatif dengan pendekatan cross sectional. Pengumpulan data menggunakan teknik sampling purposive dengan responden sebanyak 224 orang di Jakarta Timur dengan kriteria mempunyai hubungan seks antar lelaki dalam 6 bulan terakhir, bisa membaca dan menulis, not a transvestite dan mau berpartisipasi. Perilaku seks, harga diri , pengendalian diri, diukur menggunakan kuesioner mandiri yang diisi oleh responden ditemani oleh pembantu peneliti. Analisis data dilakukan untuk menentukan proporsi perilaku seks yang berisiko berdasarkan harga diri dan pengendalian diri. Hampir seluruh responden mempunyai perilaku seks yang berisiko tinggi (78,1%). Kira-kira 45,1% responden mempunyai harga diri yang rendah dan 60,7% mempunyai pengendalian diri. LSL dengan pengendalian diri mempunyai faktor risiko yang tinggi dibandingkan dengan control (p=1,000). LSL dengan harga diri yang rendah mempunyai risiko yang lebih tinggi dibandingkan dengan LSL yang mempunyai harga diri yang tinggi (OR 1,95% CI 1,00-3,80). Harga diri yang rendah pada LSL cenderung meningkatkan risiko perilaku seks maka direkomendasikan untuk mengembangkan mode konseling dan mentoring yang berisi peningkatan harga diri.Kata kunci: LSL, Perilaku seks, harga diri, pengendalian diri